2011
DOI: 10.1093/ndt/gfr307
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width is an independent predictor of mortality in acute kidney injury patients treated with continuous renal replacement therapy

Abstract: Our study demonstrates that RDW could be an additive predictor for all-cause mortality in AKI patients on CRRT treatment in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 31 publications
9
119
4
1
Order By: Relevance
“…8 Recently, RDW not only has been suggested to be related with cardiovascular disease mortality in the general population 9,10 , but also has been treated as an independent predictor of mortality in patients with heart failure, 11 stroke, 12 pulmonary arterial hypertension 13,14 and acute kidney injury. 15 Tsuboi et al also found that RDW was significantly associated with increased all-cause mortality in DM patients. 16 It is known that DM is a chronic condition with increased oxidative stress and vascular inflammation while RDW is also found to be associated with some inflammatory cytokines, and oxidative stress has been known to play a major role in the pathogenesis of renal function damage through some inflammatory markers.…”
Section: Introductionmentioning
confidence: 93%
“…8 Recently, RDW not only has been suggested to be related with cardiovascular disease mortality in the general population 9,10 , but also has been treated as an independent predictor of mortality in patients with heart failure, 11 stroke, 12 pulmonary arterial hypertension 13,14 and acute kidney injury. 15 Tsuboi et al also found that RDW was significantly associated with increased all-cause mortality in DM patients. 16 It is known that DM is a chronic condition with increased oxidative stress and vascular inflammation while RDW is also found to be associated with some inflammatory cytokines, and oxidative stress has been known to play a major role in the pathogenesis of renal function damage through some inflammatory markers.…”
Section: Introductionmentioning
confidence: 93%
“…infarction (11,13), stroke (8), cancer (26), trauma (20), chronic obstructive pulmonary disease (22), community-acquired pneumonia (15), acute kidney injury (19), pulmonary arterial hypertension (16), peripheral arterial disease (14), and critical illness (17) as well as unselected hospitalized patients (6,21) and the general nonmedical nationally representative US population (9,12). Associations of RDW with nonfatal events and outcomes have also been found, including risk of incident heart attack (10, 23), incident heart failure (10, 23), heart failure hospitalization (5, 7), 10-year coronary heart disease diagnosis (12), atrial fibrillation (10), stroke (10), cancer stage (26), complicated hospitalization (15), length of hospital stay (24), bloodstream infection (17), major bleeding (27), vascular complications (27), and many other outcomes.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Similar to our study, Hyung et al observed that RDW significantly correlated with WBC count in patients with acute kidney injury. 30 These results suggested that as RDW level.…”
Section: Discussionmentioning
confidence: 87%